Bilateral posterior scleritis after sequential bilateral cataract surgery: a case report - Chae-Min Hong; Min-Ho Shin; Seong-Jae Kim; Seong-Wook Seo; Inyoung Chung; Woong-Sun Yoo (BMC Ophthalmology, 2022)
Abstract Background Posterior scleritis is a rare, inflammatory ophthalmic disease, leading to severe visual impairment if untreated. Posterior scleritis occurring after surgery, unrelated to systemic inflammatory diseases, is even rarer. This report discusses a case of bilateral posterior scleritis, after cataract surgery in both the eyes, treated with high-dose steroids. Case presentation A 55-year-old man, who had undergone bilateral sequential cataract surgery one week before, presented with sudden loss of vision and ocular pain in both eyes. The patient had no systemic diseases or neurological symptoms. Serous retinal detachment of the macula with optic disc swelling was observed on fundus examination in both the eyes, and bilateral thickening of choroid and sclera was seen in ultrasonography. Under diagnosis of bilateral posterior scleritis due to the increased signal of sclera in both the eyes on magnetic resonance imaging, high-dose steroid therapy was performed. After treatment, improvement in visual acuity and retinal detachment were observed, and thereafter, it has been maintained without relapse. Conclusions With high-dose steroid therapy, we successfully treated a rare case of bilateral posterior scleritis following cataract surgery in both eyes. To our knowledge, this is the first report on posterior scleritis occurring after surgery, unrelated to systemic inflammatory diseases.